Saprotrophic and Ectomycorrhizal Fungi Contribute Differentially to Organic P Mobilization in Beech-Dominated Forest Ecosystems - Müller, Karolin; Kubsch, Nadine; Marhan, Sven; Mayer-Gruner, Paula; Nassal, Pascal; Schneider, Dominik; Daniel, Rolf; Piepho, Hans-Peter; Polle, Andrea; Kandeler, Ellen (Frontiers in Forests and Global Change, 2020)
Phosphorus (P) is an essential nutrient, but European forest ecosystems are experiencing widespread declines in soil P concentrations. To clarify the roles of ectomycorrhizal (EM) and saprotrophic (SAP) fungi in P cycling in forest soils that differ in inorganic and organic P availability, we conducted an ingrowth tube (IGT) experiment over 18 months of exposure in five beech (Fagus sylvatica L.) forests in Germany. To separate the contributions of both fungal guilds in situ, two different types of IGTs were used: (i) open IGTs with micromesh windows to allow EM fungi to regrow into the tubes, and (ii) closed IGTs (without mesh windows) in which recolonization by EM hyphae was restricted. We then measured phosphatase and oxidase activities in EM (open IGTs) and SAP (closed IGTs) dominated fungal assemblages. Our results show that shifts in fungal assemblages occurred over time, but that the speed and extent of those shifts differed. In three forest sites fungal community composition shifted towards greater dominance of EM fungi in open IGTs after a period of 18 months, but these changes were not apparent in two other sites. Although shifts in fungal community composition were noticeable between treatments, we found no effect on phosphomonoesterase activity. Since phosphomonoesterase is present in both fungal guilds, this indicates functional redundancy. Phosphodiesterase activity was slightly reduced in SAP dominated IGTs, indicating that SAP fungi contribute to phosphodiesterase activity to a lesser extent than do EM fungi. P cycling enzymes did not appear to have been influenced by the total P stocks of the forest sites but may have been affected by additional abiotic factors. Contrary to our expectation, phenoloxidase activity was unaffected by fungal community composition, and only peroxidase activity was higher in SAP dominated IGTs, indicating that the contribution of EM fungi to degradation of complex organic material is driven by the need to obtain nutrients in addition to C. Overall, the results of this study contribute to a better understanding of the roles of EM and SAP fungi in P cycling in forest soils.